Competencies influencing extension workers' job performance in relation to the good agricultural practices in Malaysia - Tiraieyari, Neda; Idris, Khairuddin; Uli, Jegak; Hamzah, Azimi (Science Publications, 2010)
Problem statement: The bottom line in agricultural trade is that manufacturers are demanding agricultural products that are produced in a sustainable way and with assurance that they are truly conforming to the standards of Good Agriculture Practice. Towards this objective, attention has been given on sustainable agricultural productions in Malaysia. This study is an attempt to investigate job performance of extension workers in terms of competency in relation to the Good Agricultural Practices. This research investigates the influence of competencies on extension workers’ job performance at the department of agriculture in Malaysia with the emphasis of having both human development competencies and technical competencies in order to perform extension job. Approach: Stratified random sampling technique employed to select 210 extension workers from the Department of Agriculture in four states of Malaysia. A structured research instrument was utilized to survey extension workers’ competency and job performance. To test the extent research data support the MLR model, Enter regression method was used. Results: Results showed that out of the nine competencies included in the regression model only four competencies contributed significantly in explaining the variation of job performance. The R2 value of 0.544 implies that the nine predictors explain about 54.4% of the variance in the extension workers' job performance. Conclusion/Recommendations: The findings suggest that the data dose not fully support the proposed nine-predictors multiple linear regression model. Finding was contrary to the expectations, since human development areas of competencies did not contribute to the job performance. Hence extension workers are not much involved in human development aspects of their job and they give primary attention to technology transfer rather than human development.